2000
DOI: 10.1111/j.1574-6968.2000.tb09095.x
|View full text |Cite
|
Sign up to set email alerts
|

A new beginning with new ends: linearisation of circular chromosomes during bacterial evolution

Abstract: Bacterial circular chromosomes have sporadically become linearised during prokaryote evolution. Unrelated bacteria, including the spirochete Borrelia burgdorferi and the actinomycete Streptomyces, have linear chromosomes. Linear chromosomes may have been formed through integration of linear plasmids. Linear chromosomes use linear plasmid strategies to resolve the 'end-of-replication problem', but they have generally retained from their circular ancestors a central origin of replication. Streptomyces linear chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Thus, the condition of a strict structural conservation is unnecessary for telomere evolution. The ability to easily resolve the Bendreplication problem^appears to be a universal property of life, since bacterial circular chromosomes have sporadically become linearized during prokaryote evolution (Volff & Altenbuchner 2000) and sequence patterns at the ends of the linear genome of an archaeal virus is reminiscent of eukaryotic telomeric ends (Prangishvili & Garrett 2004). Regarding yeast telomere evolution, we propose that RNA template mutations conforming to a certain level of TG-richness and protein binding specificity have been frequently fixed in yeast populations.…”
Section: On the Evolution Of Telomere Dna-binding Proteinsmentioning
confidence: 98%
“…Thus, the condition of a strict structural conservation is unnecessary for telomere evolution. The ability to easily resolve the Bendreplication problem^appears to be a universal property of life, since bacterial circular chromosomes have sporadically become linearized during prokaryote evolution (Volff & Altenbuchner 2000) and sequence patterns at the ends of the linear genome of an archaeal virus is reminiscent of eukaryotic telomeric ends (Prangishvili & Garrett 2004). Regarding yeast telomere evolution, we propose that RNA template mutations conforming to a certain level of TG-richness and protein binding specificity have been frequently fixed in yeast populations.…”
Section: On the Evolution Of Telomere Dna-binding Proteinsmentioning
confidence: 98%
“…3b). It has been observed that the ends of linear chromosomes represent regions of enhanced genomic plasticity (Chen et al, 2002;Volff and Altenbuchner, 2000). For example, linear chromosomes can undergo interchromosomal recombination between short homologous segments which might lead to the translocation of chromosomal blocks (Chen et al, 2002;Volff and Altenbuchner, 2000).…”
Section: Differences and Similarities Between The Linear Chromosomes mentioning
confidence: 99%
“…Thus, it appears that the ends of linear Agrobacterium chromosomes seem to be less well conserved compared to central parts of these replicons. It has been discussed that enhanced plasticity at the ends of linear chromosomes might facilitate genome adaptation and rearrangements (Volff and Altenbuchner, 2000). A prerequisite for the development of linear chromosomes is the existence of a telomerase gene (telA) in the genome.…”
Section: Differences and Similarities Between The Linear Chromosomes mentioning
confidence: 99%
“…Streptomycetes are mostly known as the representative antibioticproducing prokaryotic group, while many other interesting features such as morphological differentiation including mycelial growth and formation of arthrospores, and genetic properties including linear chromosomes and genetic instability, have also been the subjects of scientific interests (Locci, 1987;Volff and Altenbuchner, 2000;Chen et al, 2002). The production of antifungal substances is a common phenomenon among streptomycetes, as a number of such substances have been discovered to date (Table 1).…”
Section: Streptomyces Neopeptinius Neopeptinmentioning
confidence: 98%